2011
DOI: 10.2119/molmed.2011.00129
|View full text |Cite
|
Sign up to set email alerts
|

Myeloid Angiogenic Cells Act as Alternative M2 Macrophages and Modulate Angiogenesis through Interleukin-8

Abstract: Endothelial progenitor cells (EPCs) promote angiogenesis, and clinical trials have shown such cell therapy to be feasible for treating ischemic disease. However, clinical outcomes have been contradictory owing to the diverse range of EPC types used. We recently characterized two EPC subtypes, and identified outgrowth endothelial cells as the only EPC type with true progenitor and endothelial characteristics. By contrast, myeloid angiogenic cells (MACs) were shown to be monocytic cells without endothelial chara… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
141
0
2

Year Published

2013
2013
2018
2018

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 165 publications
(152 citation statements)
references
References 51 publications
(56 reference statements)
5
141
0
2
Order By: Relevance
“…Furthermore, MSC-induced M2 polarization was evident in both direct and indirect coculture systems, indicating that the alteration of macrophage phenotype was mediated through paracrine mechanisms. Screening of the coculture supernatants detected the presence of MSC-derived EGF, GM-CSF, CXCL1, IL-6, IL-8, MCP-1/CCL2, PDGF-AA, and RANTES/ CCL5, all of which, except for EGF, GM-CSF, CXCL1, and PDGF-AA, have previously been shown to promote M2 polarization (1,6,39,48,55). Interestingly, CXCL1 was only detected in the direct coculture system, indicating that its production required direct cell-to-cell contact.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, MSC-induced M2 polarization was evident in both direct and indirect coculture systems, indicating that the alteration of macrophage phenotype was mediated through paracrine mechanisms. Screening of the coculture supernatants detected the presence of MSC-derived EGF, GM-CSF, CXCL1, IL-6, IL-8, MCP-1/CCL2, PDGF-AA, and RANTES/ CCL5, all of which, except for EGF, GM-CSF, CXCL1, and PDGF-AA, have previously been shown to promote M2 polarization (1,6,39,48,55). Interestingly, CXCL1 was only detected in the direct coculture system, indicating that its production required direct cell-to-cell contact.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, given that expression of CSF-1 and CD163 distributed in the perivascular endothelium, which appeared only in proliferating IHs, it is possible that M-CSF-induced M2-polarised macrophage activation was mediated by proliferative endothelial cells. On the other hand, mounting evidence reveals17 33 34 that TAMs can release a number of potent proangiogenic factors, such as VEGF, TNF-a, IL-8 and bFGF, thereby promoting tumour angiogenesis. In our study, M2-polarised macrophages were found to express VEGF, which distributed in the perivascular sites of IHs.…”
Section: Discussionmentioning
confidence: 99%
“…In OIR, oxygen deprivation of the retinal glia and neurons drives expression of pro-angiogenic growth factors (such as VEGF, erythropoietin, TNF-alpha, and angiopoietin-2) and the neovascular membranes that ensue are similar to those occurring in PDR (Connor et al, 2009). The model has been extensively used for assessment of anti-angiogenic agents (Gardiner et al, 2003a;Gebarowska et al, 2002;Hammes et al, 1996;McVicar et al, 2011) and cell therapies Medina et al, 2011). In addition, a degree of BRB breakdown, glial and neuronal damage have been observed in the OIR model (Vessey et al, 2011).…”
Section: Modelling Diabetic Retinopathymentioning
confidence: 99%